Influence of social media on consumers' food choices / Chemah Tamby Chik... [et al.] - Tamby Chik, Chemah; Zulkepeley, Afiq; Tarmizi, Firdaus; Bachok, Sabaianah (UiTM Cawangan Johor, 2019)
Social media is known as a social networking platform that allows all users either on application or website to share and create content. It can be a very convenient social platform for users to share and find information regarding food. With this social media application and the advanced digital environment, users' opportunity to share and search for food has widened. This study emphasises on identifying the relationship of audio and visual appearance, information sharing and delivery, and how peer pressure factor can influence food choices through social media. An online query form for obtaining all the dataset was distributed to students in UiTM Puncak Alam as our population. Data were analysed using Statistical Package for Social Science (SPSS) (V22) and results were obtained and described using descriptive statistics and Pearson Correlation test. In total, 350 data were obtained from the total number of population selected. This study shows that audio and visual appearance are the most influential factors in people's food choices.